Preaponeurotic Fat Advancement in Levator Recession for Treatment of Upper Eyelid Retraction. Issue 4 (April 2015) - Lee, Ju-Hyang; Kim, Yoon-Duck; Woo, Kyung In; Johnson, Owen N.
Abstract : Background: Postoperative cosmetic deformities can be encountered after surgical treatments for upper eyelid retraction. The authors described a preaponeurotic fat advancement technique and investigated the effectiveness in patients who underwent levator recession for upper lid retraction. Methods: This retrospective comparative case series included 44 patients (57 eyelids) who underwent levator recession surgery with (flap group, n = 31) or without (no-flap group, n = 26) the preaponeurotic fat advancement flap procedure. Comparisons of the marginal reflex distance 1, palpebral fissure, upper palpebral fissure area, pretarsal show, eyelid asymmetry, and cosmetic complications were made between the two groups. Lid position outcomes (good, fair, and poor), which were grouped according to eyelid asymmetry, marginal reflex distance 1, and the position of upper eyelid margin, and cosmetic complications were assessed. Results: In the flap group, lid position outcomes were graded as good in 16 patients (72.7 percent), fair in four patients (18.2 percent), and poor in two patients (9.1 percent). In the no-flap group, lid position outcomes were good in 15 patients (68.2 percent), fair in five patients (22.7 percent), and poor in two patients (9.1 percent). There were no differences between the two groups in achieving acceptable eyelid lowering and eyelid symmetry (90.9 percent in both groups). However, cosmetic outcomes demonstrated some differences. There were no multiple lid creases in the fat advancement group, compared with six eyes (23.1 percent) without fat advancement. Conclusion: Preaponeurotic fat advancement flap is an effective method with which to prevent unintended multiple lid creases and provide satisfactory cosmetic outcomes in levator recession. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III.